PENGARUH MANAJEMEN KURIKULUM DAN KINERJA GURU TERHADAP HASIL BELAJAR PESERTA DIDIK - Ernawati, Ernawati; Zamroni, Zamroni; Sabran, Sabran (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
The quality of education is influenced by various factors, including policies, curriculum, and school conditions, with student learning outcomes serving as the primary indicator of success. This study aims to analyze the influence of curriculum management and teacher performance on student learning outcomes at SMA Istiqomah Muhammadiyah and SMA Plus Melati Samarinda.The research method used is a quantitative approach with a survey technique, involving 78 respondents. Data analysis was conducted using simple linear regression, t-test, multiple linear regression, and simultaneous F-test. The results showed that curriculum management contributed 35.7% at SMA Istiqomah Muhammadiyah and 50.1% at SMA Plus Melati, while teacher performance contributed 29.6% and 28.6%, respectively. Overall, these two variables influenced student learning outcomes by 40% at SMA Istiqomah Muhammadiyah and 51.1% at SMA Plus Melati. These findings affirm that curriculum management and teacher performance play a significant role in improving the quality of learning. However, additional supporting factors are still needed to achieve more optimal results.